Control of Sexual Reproduction in Gibberella zeae (Fusarium roseum “Graminearum”) - Wolf, J. C. (1977)
Sexual reproduction in Gibberella zeae (Fusarium roseum) is regulated by the fungal sex hormone zearalenone, which is known to be synthesized only by species of Fusarium. The presence of cyclic adenosine 3′,5′-monophosphate (cAMP) in mycelium of this fungus has been confirmed by analyses with thin-layer and gas-liquid chromatography, fluorescent properties, ultraviolet absorption, competitive protein-binding tests, and degradation by cyclic phosphodies-terase. cAMP but not cyclic guanosine monophosphate increased both the number of perithecia formed and the incorporation of [1-(14)C]acetate into zearalenone. It is proposed that cAMP stimulates the synthesis of zearalenone which then exerts its effect directly or indirectly on formation of perithecia.